Optimal Integration of Classified Dispersed Generation Units for Loss Minimization and Voltage Profile Enhancement in Radial Distribution Networks - Yadav L.K.; KumarVerma M. (My University, 2025)
The various combination cases of the Type I, Type II and Type III DGs are proposed in the paper for network loss minimization and voltage profile enhancement. Optimal planning of Type III DG with power factor for minimum power loss is also given in the paper. Voltage deviation corresponding to individual and each combination of DGs is also presented in the paper. Various qualitative attributes of power supply improve by application of DGs. The benefits of DG may be achieved when DGs are installed at suitable location with appropriate size. The utmost role of DGs in power system is bring down of loss and strengthen the voltage at buses in distribution system. Optimal integration of DG is a swerving and concave optimization problem. Gravitational search algorithm and Particle swarm optimization hybrid metaheuristic technique is used in this paper for optimal planning of individual and various combinations of Type-I, Type-II and Type-III DGs. The optimal planning of DG by the adopted hybrid metaheuristic approach is done on 33 and 69 bus IEEE networks. © JES 2022 on-line: journal/esrgroups.org/jes